2019
DOI: 10.3390/bios9040124
|View full text |Cite
|
Sign up to set email alerts
|

Development of Aptamer-Based TID Assays Using Thermophoresis and Microarrays

Abstract: Aptamers are single-stranded oligonucleotides which can be used as alternative recognition elements for protein detection, because aptamers bind their targets with a high affinity similar to antibodies. Due to the targetinduced conformational changes of aptamers, these oligonucleotides can be applied in various biosensing platforms. In this work, aptamers directed against the vascular endothelial growth factor (VEGF) were used as a model system. VEGF plays a key role in physiological angiogenesis and vasculoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…As soon as the most suitable oligonucleotide candidate was determined, competitive assays using immobilized aptamers were carried out. We have recently used this strategy (the development of a TID assay via MST and its transfer to an aptamer-microarray format) successfully for a protein target [20]. Here, we demonstrate the suitability of the approach for aptamers directed against small molecules.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…As soon as the most suitable oligonucleotide candidate was determined, competitive assays using immobilized aptamers were carried out. We have recently used this strategy (the development of a TID assay via MST and its transfer to an aptamer-microarray format) successfully for a protein target [20]. Here, we demonstrate the suitability of the approach for aptamers directed against small molecules.…”
Section: Resultsmentioning
confidence: 87%
“…The CD spectroscopy indicated that the target might bind to a preformed structural motif of the aptamer. In other published competitive assays, we have already been able to successfully use the 10-nt length [15,20]. Moreover, it could be shown that longer oligonucleotides lead to decreased complementary strand displacement and consequently decreased sensing performance [25].…”
Section: Design and Evaluation Of Complementary Oligonucleotidesmentioning
confidence: 99%
“…Schematic representation of the (A) aptamer‐based four‐color nanoprobe for simultaneous sensing and imaging of multiple tumor‐associated proteins in living cells and (B) aptamer‐based VEGF detection by TID of the fluorescently labeled complementary oligonucleotide. Figures were reproduced from Xu et al 245 (A) and Kurth et al 246 (B) with permission. AFP, ɑ‐fetoprotein; CEA, carcinoembryonic antigen; HER2, human epidermal growth factor receptor 2; TID, target‐induced dissociation; VEGF, vascular endothelial growth factor [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Dna‐based Aptasensors For Vegf Detectionmentioning
confidence: 99%
“…In the presence of VEGF 165 , the formation of the aptamer‐protein complex favored the release of the complementary strand, resulting in a detectable decrease of the fluorescence intensity (Figure 13B). The proposed aptamer‐microarray allowed a LOD of 0.1 nM for VEGF 165 246 …”
Section: Dna‐based Aptasensors For Vegf Detectionmentioning
confidence: 99%
See 1 more Smart Citation